ANALISIS PENGARUH DIMENSI KOMPONEN ALAT ANGKAT KENDARAAN NIAGA TERHADAP BIAYA PRODUKSI - Yaroso Y. Mirino; Fentje Abdul Rauf; Rudy Poeng (JURNAL POROS TEKNIK MESIN UNSRAT, 2012)
In machining industry it is essential to know the cost of the product. By knowing the price of the product the profil could be calculated. Hoisting equipment is very helpful in car maintenance or repair, the purpose of this study is to measure working time, analyze the cost of the production of a 2 ton car hoisting equipment manufactured by students of mechanical Engineering University of Sam Ratulangi. Â  From the results of the analysis, prices lifting equipment sales in the commercial vehicle production Mechanical Engineering student Sam Ratulangi University, is Rp 1,388,371 per unit. This shows that the price obtained is still less than the price of one unit of a triple lift lifting equipment types in the market internet, Rp. 1,745,145 per unit.